Vocational Education and Training and the Labour Market : a Comparative Analysis of China and Germany - Schnarr, Alexander [Verfasser]; Yang, Sun [Verfasser]; Gleißner, Kai [Verfasser] (inWEnt, 2008)
This publication "introduces the approaches and models of using the (vocational) education system to train skilled workers in order to meet labour market needs from both the German and the Chinese perspective, taking into account different cultural backgrounds, legal frameworks as well as historical and recent developments within the education system of both countries. The following areas are considered in detail: (1) Which implications do the political frameworks of both China and Germany hold for the respective education systems and the access to the labour market? (2) How are the vocational education and training systems in both countries organized? What are the legal foundations, how are the systems structured, which role does skills assessment play in achieving labour market compatibility? (3) What are the strengths and weaknesses of both systems regarding labour market access? Which implications can be drawn from the comparison of both countries?" (Herausgeber, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 1.2 Arbeitsmarkt; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; I 2.1 Deutschland; I 2.3.4 Asien; Berufsbildungssystem; Berufsbildungspolitik; Beziehung Bildungssystem Beschäftigungssystem; Arbeitsmarkt; Berufseinmündung; Zweite Schwelle; Internationaler Vergleich; Bundesrepublik Deutschland; China